CENTRAL NEUROTHAKEOMA OF MANDIBLE - Bajpai, Manas; Pardhe, Nilesh (Journal of Ayub Medical College Abbottabad, 2015)
A Sixty year old lady presented to the Department of Oral medicine and Radiology with the chief complain of asymptomatic swelling in the left back region of the lower jaw of two years duration. Both the past medical history and systemic signs are not relevant with the case. Extraoral examination did not reveal any abnormality. Intra oral examination revealed a hard swelling on the left side of the alveolar region of the posterior mandible. The three dimensional computed tomography demonstrated a large well defined homogenous attenuated soft tissue density lesion of approximately 54 Ã— 46 Ã— 44 mm. Lesion producing a mass effect over adjacent tongue and musculature. Provisional diagnosis of ameloblastoma was made. Excision of the lesion under local anaesthesia was done and the growth was easily malleted out. The histopathological diagnosis of central/ Intra osseous neurothakeoma was given. Post operative follow up of the patient is uneventful.